Care of Older Adults with Mental Illness in Long-Term Care Residential Facility: A Scoping Review - Čížková, Jana; Dostálová, Vladimíra; Bártová, Alžběta; Holmerová, Iva; Valeš Jelínková, Petra (Journal of the American Medical Directors Association, 2024)
OBJECTIVES: Mental illness affects approximately 1 in 8 people globally, with approximately 15% of adults aged 60 years and older experiencing a mental disorder. With the aging population, there is a growing demand for long-term care. This scoping review focuses on older adults with non-neurocognitive and non-neurodevelopmental mental illnesses (NNNDMIs) in nursing homes, exploring how the care is provided. DESIGN: A scoping review. SETTING AND PARTICIPANTS: The review includes studies addressing care for older adults with NNNDMI in nursing homes. METHOD: The PRISMA-ScR protocol was followed. Four research databases (EBSCO, PubMed, Web of Science, and Scopus) and article bibliographies were used for the literature search. Thematic analysis identified the main themes. RESULTS: From a total of 1948 search results, 13 articles were analyzed to reveal 5 themes: (1) challenges and recommendations in nursing home admission for older adults with mental illness; (2) impact on the quality of the care; (3) need for specialized staff training and competency; (4) contributions to psychiatric and behavioral symptoms; and (5) need for a range of interventions. CONCLUSION AND IMPLICATIONS: Older adults with NNNDMI face barriers during admission to long-term care facilities that highlight concerns about care quality and systemic issues. Behavioral symptoms require specialized mental health support, but access to such services is lacking. Deficiencies in staff education and burnout prevention initiatives further underscore the need for comprehensive reforms to address the unique needs of this overlooked population in long-term care settings.
Keywords: ženské pohlaví; Female; senioři nad 80 let; Humans; lidé; Mental Disorders; Nursing Homes; Long-Term Care; Aged; dlouhodobá péče; Aged, 80 and over; pečovatelské domovy; duševní poruchy; Male; senioři; mužské pohlaví